Study of Academic Achievement and Adjustment of Secondary School Students in Relation to Working Status of Mothers - Patel, Hemlata; SINGH, VIVEK (JOURNAL OF INDIAN EDUCATION, 2017)
The present study is an attempt to identify the role of working and non-working mothers on the academic achievement and adjustment of their children. The research was conducted in Itanagar Complex, Arunachal Pradesh, India. A total of 187 students (95 boys and 92 girls) were selected from public and private secondary schools through simple random sampling, as respondents. The tools used to measure the variables under study were Adjustment Inventory for school student and academic percentage marks obtained in Class X. The students’ t-test analyses were conducted to determine the association among the variables identified in the study. After the analysis of data, it was found that the academic achievement of male and female students of working and non-working mothers did not differ significantly. However, a significant difference was observed in the educational adjustment. Further, there was no significant difference in the social and emotional adjustment of boys and girls of the non-working mother.